Multicriteria wind potential assessment using fuzzy logic in decision making: A case study of Iran. Issue 12 (11th May 2021) - Aryanfar, Amin; Gholami, Aslan; Pourgholi, Mahdi; Zandi, Majid
Abstract: The current paper introduces an innovative multicriteria wind potential assessment study using fuzzy logic in decision making. Regarding the diverse conditions and lack of comprehensive studies, Iran was selected as a case study, and by applying the proposed framework, all the 559 synoptic meteorological stations in the country were studied. Fourteen technical, eco‐environmental, and social indicators were defined for the assessment. Each of the indicator's effectiveness was determined using related literature and interviews with local experts. Finally, using fuzzy logic in decision making, all the selected sites and the provinces were scored and ranked. Moreover, the priority maps of Iran provinces considering social and eco‐environmental aspects were provided. The selected sites' final standing for the development of offshore and onshore wind power plant was also determined. The results indicate that taking just the technical conditions into account can result in misleading conclusions and social and eco‐environmental criteria must also be considered for potential assessment studies. Moreover, it was shown that equal supportive policies for wind development throughout the country would mitigate their efficiency. Therefore, the energy strategies should be codified, considering local circumstances to organize investment resources, leading to higher legislation efficiencies and faster development.